The Relationship Between Anxiety Levels And Blood Pressure In Hypertensive Patients At Krung Barona Jaya Community Health Center, Aceh Besar - Sahara Sahara; Maulidia Maulidia; Sarina Putri; Alda Nabila; Dina Ramadhana; Tiarnida Nababan (CV. AFDIFAL MAJU BERKAH, 2026)
Hypertension, a serious global health issue, often leads to serious consequences, including heart disease and stroke. This study examined the impact of psychological variables, particularly anxiety, on blood pressure among patients at the Krung Barona Jaya Community Health Center in Aceh Besar. The study was done using a quantitative cross-sectional design. Data were taken from 60 respondents, they were chosen by purposive sampling, not random. The researchers applied the Hamilton Anxiety Rating Scale (HARS) to check anxiety level, and also used a sphygmomanometer to record blood pressure in a direct way. From the results, about 38.3% respondents showed moderate anxiety, meanwhile 61.7% were in severe anxiety condition, which is quite high. For blood pressure status, exactly 50% respondents had hypertension, and the other 50% did not show hypertension at the time of data collection. Then, using Chi-Square test with significance level 0.05, the p-value was 0.013. This value is smaller than 0.05, so it means there is a significant relationship, even if the sample is not very large. In short conclusion, both variables are connected. When anxiety level becomes higher, the risk for hypertension also tends to increase, it looks proportional in this sample, even in simple field condition like local clinic setting.